Study of Potential in vitro Antidiabetic Activities of Methanolic Extracts of Memordica charantia, Nyctanthes arbor, and Tinospora cordifolia from Dang Nepal - Chemjong, Kabin; Sharma, Tripti; B.K., Bijaya; Paudel, Rajesh; Subba, Bimala (Journal of Institute of Science and Technology, 2025)
A wide diversity of medicinal plants rich in phytochemicals are the potential source of drugs. The phytochemical composition of plants varies with the geographical location. These selected medicinal plants containing phytochemicals inhibit the catalytic action of α-amylase to ameliorate the complications of diabetes. The main goal of this work is to compare the phytochemical composition and biological activities such as antioxidant, toxicity, and α-amylase inhibitory activity of Memordica charantia, Nyctanthes arbor, and Tinospora cordifolia. The study employed qualitative analysis through phytochemical screening, followed by quantitative measurement of total phenolic and flavonoid content by using the Folin-Ciocalteu reagent and colorimetric method. Additionally, biological activities were assessed using the 2,2 diphenyl-1-picrylhydrazyl antioxidant assay, α-amylase starch iodine method, and brine shrimp lethal test. The study revealed that the total phenolic contents in T. cordifolia, M. charantia, and N. arbor were measured as 140.49, 101.69, and 98.76 mg GAE/g, respectively. Consequently, N. arbor, T. cordifolia, and M. charantia showed strong antioxidant properties, with IC50 values of 48.16, 45.07, and 69.34 μg/mL, respectively. Furthermore, in the brine shrimp lethal test, all the extracts exhibited low toxicity, with the LC50 value of M. charantia (316.22 μg/mL), N. arbor (275.42 μg/mL), and T. cordifolia (275.42 μg/mL), respectively. GC-MS analysis of hexane fraction of N. arbor methanol extract reveals the presence of compounds like Hexanoic acid, 6-amino-6-oxo-, and Benzo[b]thiophene-2- carboxamide,3-chloro-N-(2-bromophenyl). Therefore, in all the aspects of the study, the methanolic extract of M. charantia, N. arbor, and T. cordifolia were potent, which concludes that these extracts contain abundant phytochemicals and possess diverse biological activities.